De novo coiled-coil peptides as scaffolds for disrupting protein–protein interactions. Issue 39 (22nd August 2018) - Fletcher, Jordan M.; Horner, Katherine A.; Bartlett, Gail J.; Rhys, Guto G.; Wilson, Andrew J.; Woolfson, Derek N.
Abstract : Homo- and hetero-dimeric coiled coils as scaffolds for the presentation of α-helical protein-binding motifs. Abstract : Protein–protein interactions (PPIs) play pivotal roles in the majority of biological processes. Therefore, improved approaches to target and disrupt PPIs would provide tools for chemical biology and leads for therapeutic development. PPIs with α-helical components are appealing targets given that the secondary structure is well understood and can be mimicked or stabilised to render small-molecule and constrained-peptide-based inhibitors. Here we present a strategy to target α-helix-mediated PPIs that exploits de novo coiled-coil assemblies and test this using the MCL-1/NOXA-B PPI. First, computational alanine scanning is used to identify key α-helical residues from NOXA-B that contribute to the interface. Next, these residues are grafted onto the exposed surfaces of de novo designed homodimeric or heterodimeric coiled-coil peptides. The resulting synthetic peptides selectively inhibit a cognate MCL-1/BID complex in the mid-nM range. Furthermore, the heterodimeric system affords control as inhibition occurs only when both the grafted peptide and its designed partner are present. This establishes proof of concept for exploiting peptides stabilised in de novo coiled coils as inhibitors of PPIs. This dependence on supramolecular assembly introduces new possibilities for regulation and control.